ONLINE LEARNING OF INDONESIAN LANGUAGE IN PRIMARY SCHOOL (MADRASAH IBTIDA’IYAH) ON INSTRUCTION TEXT IN COVID-19 PANDEMIC - Sinsin Nurhayati; Enung Nurhayati (JLER (Journal of Language Education Research), 2021)
The research aimed to described (1) Online learning scenarios which is doing by teachers during the COVID-19 pandemic on instruction text learning, (2) Difficulties of students and teachers experience when implementing on instruction text learning in the pandemic,(3) Student and teacher responses to online learning during the pandemic on instruction text learning, and  (4) Differences in students’ knowledge and skills of instruction text learning in online learning. The research was conducted for 1 month in September 2020. The subjects of study are two teachers and fourth grade students of MI Muhammadiyah 2. The research procedure used was descriptive statistics. Data collection techniques in this research through online interviews. The results of MI Muhammadiyah 2 online learning research during the COVID-19 pandemic show that : (1) Online learning scenarios which is doing by teachers during the COVID-19 pandemic are Distance Learning and continue to make lesson plants that are simply arranged and contain the main things including pre–activities, core activities and post–activities. (2) Difficulties of students and teachers experience when implementing on the instruction text learning in the pandemic were 80% in the moderate category and 20% in the low category, 3) Student and teacher responses to online learning during the  COVID-19 pandemic was 20% showing positive responses, 40% showed neutral responses and 40% showed negative responses. (4)The results of the calculation of Asymp (2 – Failed) reached 0,118. The data shows that 0,118 is greater than 0,05. So it can be concluded that students have different knowledge and skills of instruction text learning in online learning Keywords: distance Learning, COVID-19, Online learning